Kajian Sengketa Pajak Atas Impor Bahan untuk Pakan Ternak/Pakan Ikan Sebagai Barang Kena Pajak Tertentu yang Dibebaskan dari Pengenaan Pajak Pertambahan Nilai - Diana M. Ginting (Publikasi Indonesia, 2025)
One of the objects of VAT is the import of Taxable Goods (BKP) which is collected by the Directorate General of Customs and Excise (DJBC). On the other hand, certain BKP imports are exempt from the imposition of VAT. One of the certain BKP imports that are exempt from the imposition of VAT is the import of materials for animal feed/fish feed. In the import of materials for animal feed/fish feed, there are different views between the importer and the DJBC whether they are subject to VAT or exempt from VAT, which continues to be a tax dispute that is resolved in the realm of justice. The main problem in this study is: (i) What is the substance of the tax dispute over the import of materials for animal feed/fish feed as certain BKP imports that are exempt from the imposition of VAT? (ii) How is the taxation regulation on the import of materials for animal feed/fish feed as a certain BKP? (iii) What efforts can be made to reduce the problem of taxation on the import of materials for animal feed/fish feed as certain Taxable Goods? The method used in this study is a literature study using qualitative descriptive analysis related to the import of materials for animal feed/fish feed as certain BKPs that are exempt from the imposition of VAT. An effort to reduce tax disputes over the aspect of taxation/VAT on the import of materials for animal feed/fish feed is that DJBC needs to evaluate the implementation of PMK 142/PMK.010/2017. DJBC, BKF, and DGT in order to synergize in drafting amendments to PMK 142/PMK.010/2017.